Effects of Mayer's signaling principle on English grammar and writing skills of grade six pupils - Castillo, Kristine Erika Capuli
This study investigated the effects of Mayer's Signaling Principle on the academic performance of Grade Six students in a private school located in Quezon City. To answer the research questions, the researcher utilized an embedded quantitatively-driven mixed methods research design. Hence, a series of gathering quantitative and qualitative data was conducted during the data collection procedure Data gathering was divided into three phases, namely: Before the Intervention, During the Intervention, and After the Intervention, which all proved the consistency of the results and responses generated from the seventy respondents from the c:xpcrimcntal and control groups Independent samples T-test and paired samples T-test were the two major statistical tests that were used to analyze the quantitative data while focus group discussions, short answer essays, and survey questionnaires were utilized to generate qualitative data that supported the quantitative results. Initial data that emanated from each of the three phases in the data gathering procedure guided the researcher in moving forward to the next phase and in arriving at the conclusions and recommendations of the study. The findings revealed that students in the experimental group performed better in academics as shown in the results of their summative test in Language after experiencing the intervention of using signaled teaching media. Results proved a significant difference between their pretest and posttest scores after experiencing the intervention. In addition, students who were exposed to the intervention significantly performed better in the summative test than those students who were not exposed to the intervention. Looking into these major findings, clear evidence of the positive effects of Mayer's Signaling Principle on the academic performance of the students was established, hence, recommending the use of the principle when designing teaching materials for students. With the findings and recommendation, the researcher hopes that further understanding of the effects of Mayer's Signaling Principle on the learners' academic performance may be gained in order to improve quality of instructional materials.